Weighing Family Loyalty: The Challenge of Cultural Nepotism in Recruitment Policies - Arham (AMUYA: JOURNAL OF MANAGEMENT, 2026)
The management of waqf assets in South Sulawesi Province faces fundamental challenges due to suboptimal managerial capacity among Nazhir (waqf managers), resulting in assets remaining static and limited to basic religious functions (ibadah mahdah). The primary issues include low competency standards, a lack of professional certification, and the prevalence of cultural nepotism in recruitment, where appointments are based on kinship rather than technical merit. If left unaddressed, waqf assets will continue to be a maintenance burden, and public trust in waqf institutions will significantly decline. This research is a policy paper employing a descriptive qualitative analysis. To determine priority issues, the Urgency, Seriousness, and Growth (USG) method was applied. Furthermore, a Fishbone diagram was utilized to identify the root causes of problems within the Nazhir recruitment process. The study is framed by several theoretical lenses, including Human Capital Theory, Stewardship Theory, Resource-Based View (RBV), Institutional Theory, and Public Accountability Theory. The analysis reveals that recruitment issues driven by cultural nepotism are the highest priority, evidenced by the highest USG score (15 points). Factors such as kinship-based appointments, the absence of systematic fit and proper testing at the Office of Religious Affairs (KUA), and optional certification regulations act as major barriers to professionalism. This paper recommends a policy intervention through the issuance of a Ministerial Regulation (PMA) to mandate professional competency certification for Nazhir, thereby breaking the cycle of nepotism and fostering a sustainable transformation toward productive waqf.